Temperature Control and Scheduled Feeding for Quail with Optional Control - Hail Kaharuddin, Muhamad Amzar; Masek, Alias (Research and Innovation in Technical and Vocational Education and Training, 2023)
Quail chicks are delicate and require careful attention, as they have a tendency to die easily, particularly in their first 1-2 weeks of life. To aid in monitoring the environment for quail, a prototype for controlling quail food and temperature has been developed. The design thinking model, which consists of five stages - Empathize, Define, Ideate, Prototype, and Test - was used by the researcher in the development of this prototype. Information about quail and the development of the prototype is explained in this writing. The five phases of Design Thinking have been applied in the development of the quail food and temperature control prototype. The prototype uses temperature, food and water level detectors, and utilizes an arduino uno microcontroller and NodeMCU to connect to the Blynk app as a display for remote monitoring. The prototype is designed to control the temperature in the quail cage by using a DHT11 temperature detector with a heating bulb. The food quantity is detected with a load cell, which indicates if the food is sufficient or not. The water level detector uses a float switch sensor to detect the drinking water level in the quail cage. In this writing, we delve deeper into the development of a temperature control prototype and the scheduling of quail food in a controlled manner.